Determination of ginsenoside compound K in human plasma by liquid chromatography-tandem mass spectrometry of lithium adducts - Yunhui Chen; Youming Lu; Yong Yang; Xiaoyan Chen; Liang Zhu; Dafang Zhong (Elsevier, 2015)
Ginsenoside compound K (GCK), the main metabolite of protopanaxadiol constituents of Panax ginseng, easily produces alkali metal adduct ions during mass spectrometry particularly with lithium. Accordingly, we have developed a rapid and sensitive liquid chromatography-tandem mass spectrometric method for analysis of GCK in human plasma based on formation of a lithium adduct. The analyte and paclitaxel (internal standard) were extracted from 50 µL human plasma using methyl tert-butyl ether. Chromatographic separation was performed on a Phenomenex Gemini C18 column (50 mm×2.0 mm; 5 μm) using stepwise gradient elution with acetonitrile-water and 0.2 mmol/L lithium carbonate at a flow rate of 0.5 mL/min. Detection was performed in the positive ion mode using multiple reaction monitoring of the transitions at m/z 629→449 for the GCK-lithium adduct and m/z 860→292 for the adduct of paclitaxel. The assay was linear in the concentration range 1.00-1000 ng/mL (r2>0.9988) with intra- and inter-day precision of ±8.4% and accuracy in the range of −4.8% to 6.5%. Recovery, stability and matrix effects were all satisfactory. The method was successfully applied to a pharmacokinetic study involving administration of a single GCK 50 mg tablet to healthy Chinese volunteers.